Human induced pluripotent stem cell–derived therapies for regeneration after central nervous system injury - Stephen Vidman; Yee Hang Ethan Ma; Nolan Fullenkamp; Giles W. Plant (Neural Regeneration Research)
In recent years, the progression of stem cell therapies has shown great promise in advancing the nascent field of regenerative medicine. Considering the non-regenerative nature of the mature central nervous system, the concept that “blank” cells could be reprogrammed and functionally integrated into host neural networks remained intriguing. Previous work has also demonstrated the ability of such cells to stimulate intrinsic growth programs in post-mitotic cells, such as neurons. While embryonic stem cells demonstrated great potential in treating central nervous system pathologies, ethical and technical concerns remained. These barriers, along with the clear necessity for this type of treatment, ultimately prompted the advent of induced pluripotent stem cells. The advantage of pluripotent cells in central nervous system regeneration is multifaceted, permitting differentiation into neural stem cells, neural progenitor cells, glia, and various neuronal subpopulations. The precise spatiotemporal application of extrinsic growth factors in vitro, in addition to microenvironmental signaling in vivo, influences the efficiency of this directed differentiation. While the pluri- or multipotency of these cells is appealing, it also poses the risk of unregulated differentiation and teratoma formation. Cells of the neuroectodermal lineage, such as neuronal subpopulations and glia, have been explored with varying degrees of success. Although the risk of cancer or teratoma formation is greatly reduced, each subpopulation varies in effectiveness and is influenced by a myriad of factors, such as the timing of the transplant, pathology type, and the ratio of accompanying progenitor cells. Furthermore, successful transplantation requires innovative approaches to develop delivery vectors that can mitigate cell death and support integration. Lastly, host immune responses to allogeneic grafts must be thoroughly characterized and further developed to reduce the need for immunosuppression. Translation to a clinical setting will involve careful consideration when assessing both physiologic and functional outcomes. This review will highlight both successes and challenges faced when using human induced pluripotent stem cell-derived cell transplantation therapies to promote endogenous regeneration.